EVALUATION OF USER SATISFACTION WITH THE ACCESS BY KAI APPLICATION USING THE END USER COMPUTING SATISFACTION (EUCS) AND IMPORTANCE PERFORMANCE ANALYSIS (IPA) APPROACHES - Indah Wardati; Arlina Nurbaity; Beby Karina (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
Access by KAI is the official digital application of PT Kereta Api Indonesia (Persero) that facilitates the public in booking train tickets. However, users have reported several complaints regarding the performance of certain features. This study aims to evaluate user satisfaction of the Access by KAI application using the End User Computing Satisfaction (EUCS) approach analyzed through the Importance Performance Analysis (IPA) method. The five EUCS variables used are: content, accuracy, format, ease of use, and timeliness. This research employed a quantitative method by distributing questionnaires to 239 respondents, supported by qualitative data from interviews with 15 selected respondents and analysis of user comments on the Google Play Store. The findings reveal that there are seven application features located in Quadrant I of IPA, meaning they are considered important but have low performance. These features include: post-payment user purchase data (X2.3), train schedule information (X2.4), font display (X3.4), bank payment (X4.2), ticket rescheduling (X4.7), ticket booking process (X5.2), and digital wallet payment (X5.4). Interview results and Play Store reviews further support these findings. The study recommends that PT KAI prioritize improvements to these features to enhance user satisfaction.